2012
DOI: 10.1542/peds.2012-0391
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Exergaming in Youth

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Exergaming offers a physical activity (PA) alternative for youth that may be attractive in our increasingly technophilic society. Exergaming increases PA and decreases sedentary time, but most exergame studies are clinically based and focus on measuring energy expenditure during exergaming. WHAT THIS STUDY ADDS:One-quarter of adolescents exergamed at intensity levels that could help them achieve PA recommendations. Exergamers were more likely to be female, play nonactive video gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
71
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 55 publications
8
71
1
1
Order By: Relevance
“…The children had easy access to active gaming consoles and games at home, as do New Zealand children 17 and Canadian and Dutch adolescents. 14,15 As with the Canadian adolescents, the children preferred the Nintendo Wii™ console and Nintendo Wii™ Sports game compendium. 15 In previous laboratory-based investigations this particular console and game has increased children's energy expenditure (EE) by two to three times, when compared with resting and sedentary media activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The children had easy access to active gaming consoles and games at home, as do New Zealand children 17 and Canadian and Dutch adolescents. 14,15 As with the Canadian adolescents, the children preferred the Nintendo Wii™ console and Nintendo Wii™ Sports game compendium. 15 In previous laboratory-based investigations this particular console and game has increased children's energy expenditure (EE) by two to three times, when compared with resting and sedentary media activities.…”
Section: Discussionmentioning
confidence: 99%
“…The range of laboratory protocols utilised are unlikely to resemble children's real life active gaming activity especially when considering adolescent active game-play. In Canada, adolescents reported playing for 50.5 minutes per bout 14 whilst in The…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review [25] confirms that engaging in a home exercise programme can result in improved PA participation among patients with CF. It has also been reported that many adolescents regularly play AVGs at intensity levels above global PA recommendations [26]. However, the relevant studies failed to verify the effects of using AVGs as a training protocol and to determine whether these effects are maintained after the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] A Canadian study reported that approximately 25 percent of 10th and 11th graders engaged in active gaming (based on responses to the question ''Do you play active videogames?'') and that active gamers were more likely to be girls, to also play nonactive videogames, to watch q2 hours of TV/day, and to be concerned about weight.…”
Section: Introductionmentioning
confidence: 99%